(untitled) (Heritage, 2021)
Financial policy is very important for the development of cultural heritage. Without an efficient funding system, there is no successful preservation of cultural heritage. Effective financing depends not only on the legislative policy, but also on all participants in this field, starting from the social understanding of heritage to its knowledge by potential investors. In recent years, there has been an increase in the need to preserve cultural heritage, and thus an increase in the demand for financial resources for its preservation. The reasons are, obviously, in a larger number of facilities that require renovation, expansion of works and procedures aimed at their conservation and preservation, and the decreasing volume of public finances allocated for these purposes. Cultural heritage is a public good and that is why its preservation is difficult to imagine without investing public funds. Public funding of cultural heritage has multiple positive effects for the state. The immediate effect is, of course, the preserved and restored cultural heritage, and the indirect ones are wider. These are new jobs, support for traditional crafts, development of tourism and the local economy, improvement of infrastructure and living environment. Public financing of cultural heritage must not be seen as a burden, but as an investment that will return many times over. Of course, it is necessary to focus on donors, project financing, funds from various European programs and organizations, in order to provide as much diverse financing of cultural heritage as possible in the future. The paper gives an overview of the ways of financing cultural heritage in three European countries: Germany and the Netherlands.